Estudio de factibilidad para la creaciòn de una hosterìa en el cantòn Palora de la provincia Morona Santiago. - RAMIREZ FONSECA, ROSA ELENA (2012)
Ecuador has many great tourist attraction areas that stand out for its diverse culture and rich biodiversity, among these, the central highlands and the Amazon, those with great wealth. The most frequently visited areas, is characterized by oil production, forestry, agriculture and livestock in the Amazon region, in terms of the sierra region, there is a crop, livestock and floriculture. The overall objective of this plan is to determine the feasibility of building a hostel in the canton Palora, to be entrepreneurs and creating jobs, contributing to the socioeconomic development of the city of Palora. Among the methods applied is the scientific method that allowed it to seek knowledge on valid and reliable procedures, and thus spread the knowledge of market research, technical study, Financial and Organizational Study, etc. Then release the results, the deductive-inductive method, allowed claims based on assertions character to individuals, which were compared with reality through the findings that emerged in this investigation which has served to meet the requirement of this service in the Canton province of Morona Santiago Palora., the analytical method, allowed analyzing each of the internal elements, external causes and the relationship between them which facilitates the analysis of information and data allowing to know the advantages and disadvantages carrying out this project, and the statistical method - Mathematician, facilitated the interpretation and understanding of statistics as: implementation and tabulation of the respective survey, projections, financial indicators (IRR, NPV, PE), and this possible way to know the facts about the company during the life of the same. Also applied research techniques such as Documentary Collection, which allowed collect bibliographic information through documents, graphics, dictionary, theses, magazines, among others, which served to have a broader knowledge thus to develop a better way this paper, direct collection, allowed us to determine the location, geographical location and environmental place to undertake the project, allowing the company to locate in the most convenient location for both the employer and for the service user, the survey allowed us to collect information indirectly through the development of an appropriate questionnaire to issue to thereby obtain information from various problems in the inquiry stage, will be held in order to facilitate information development and analysis of market research, which served to know the tastes and preferences of applicants in the service and therefore the best way to focus on the service to be offered, and the interview that allowed us to collect field data, using the interview orally with persons engaged in the provision of tourism services similar to the proposed project that served as sources of information for the development of this project. To demonstrate the feasibility of the implementation of this project, it is structured in a way that affects the service description, then exposed in a technical market study by analyzing the demand, supply and participation company in the market, further analyzed as market factors: product, price, place and promotion. "The organizational structure that will have the company, will enable the normal development of the same, as well, with the job description is provided meeting the objectives. The technical study determined the installed capacity of the project is the same as the service of 4,380 tourists. It also has raised the requirements of machinery, equipment, physical space and facilities to enable the normal development of the activities set; then gives in detail the required investment and distribution, financial evaluation procedure in order to establish the feasibility of project, it is determined an NPV of $ 26,375.83, an IRR of 19.63%, the RBC of 1.58, Capital Recovery in 5 years, 1 month and 11 days, a sensitivity analysis with the increase of 26 , 6% in costs and a decrease of 16.25% in revenue. Finally determined to create the Inn is incorporated to Canton Palora tourism as one of the real alternatives of sustainable development and security is a good investment that will achieve the desired success.